Pengembangan LKPD Berbasis Problem Based Learning Pembelajaran IPAS Kelas IV di SDN 03 Pontianak Selatan - Hidayat, Taufik; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research generally aims to develop and produce problem-based learning worksheet products in the natural science subject on energy in the daily life of class IV SDN 03 Pontianak Selatan. This study uses the Research and Development (RnD) research and development method with the Borg and Gall method approach, which contains seven research steps namely potentials and problems, data collection, product design, product design validation, design revision, product testing, final product revision . At the product trial stage it was carried out in class IV SDN 03 Pontianak Selatan with a total of 32 students. The results of this study are in the form of problem-based learning worksheets for students on natural science subjects on energy in everyday life. The results of the material validity test showed a percentage of 81.54% with the interpretation of